Think Pair Share With Comic For Mathematical Problem Solving Skills - Turyanto Turyanto; Denik Agustito; Sri Adi Widodo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
The purpose of this study was to find out that Think Pair Share with mathematical comics is more effective than Think Pair Share learning without using comics. The research method used is an experiment with the design of Post-test-Only Control Design. The sample size was 64 students taken using cluster random sampling technique. The instrument used in this study is the Mathematical Problem Solving Test. Data analysis techniques were used using the Wilcoxon Signed Rank Test non-parametric statistical test. The results of the study showed that the learning of Think Pair Share models by using mathematical comics was no more effective than learning Think Pair Share without using comics. Although this study shows the opposite results from existing theoretical studies, in general, the use of learning media such as mathematical comics collaborated with any model can make mathematics learning more effective.